Carrier dynamics within semiconductor nanocrystals - Fairclough, SM (2012)
This thesis explores how the carrier dynamics within semiconductor nanocrystals can be directly engineered through specific core-shell design. Emphasis is placed on how material characteristics, such as strain or alloying at a core-shell interface, can influence the exciton energies and the recombination dynamics within semiconductor nanocrystals. This study synthesises type-II heterojunction ZnTe/ZnSe core-shell nanocrystals via a diethyl zinc-free synthesis method, producing small size distributions and quantum yields as high as 12%. It was found that the 7% lattice mismatch between the core and shell materials places limitations on the range of structures in which coherent growth is achieved. By developing compositional and strained atomistic core-shell models a variety of physical and optical properties could be simulated and has led to a clear picture of the core-shell architecture to be built. This characterisation provides evidence that the low bulk modulus ZnTe cores are compressed by the higher bulk modulus smaller lattice constant ZnSe shells. Further studies show how strain is manifested in structures with 'sharp' core-shell interfaces and how intentional alloying the interface can influence the growth and exciton energies. A (2-6)-band effective mass model was able to distinguish between the as-grown 'sharp' and 'alloyed' interfaces which indicated that strain accentuates the redshift of the excitonic state whilst reduced strain within an alloyed interface sees a reduced redshift. Single nanocrystal spectroscopy investigations of brightly emitting single graded alloyed nanocrystals and of a size series of commercially available CdSe/ZnS nanocrystals showed almost no fluorescence intermittency (nearly 'non-blinking'). These investigations also identified trion recombination as the main mechanism within the blinking 'off' state. Ultimately this thesis adds to the growing understanding of how specific core-shell architectures manipulate the electronic structure and develops techniques to identify specific material characteristics and how these characteristics influence the physical and optical properties within semiconductor nanocrystals.